Acute exacerbation of COPD is associated with fourfold elevation of cardiac troponin T. Issue 2 (28th September 2012) - Søyseth, Vidar; Bhatnagar, Rahul; Holmedahl, Nils Henrik; Neukamm, Anke; Høiseth, Arne Didrik; Hagve, Tor-Arne; Einvik, Gunnar; Omland, Torbjørn
Abstract : Objective: To investigate if acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is associated with myocardial injury, expressed as elevated high sensitive cardiac troponin T (hs-cTnT), and to identify determinants of hs-cTnT in chronic obstructive pulmonary disease (COPD) patients. Design: In a cross-sectional study, hs-cTnT in patients hospitalised for AECOPD was compared with hs-cTnT in COPD patients in their stable state. Setting: The study was conducted at a teaching and a pulmonary rehabilitation clinic. Participants: Consecutive admissions to participating units for the years 2010–2011 meeting objective, standardised criteria for AECOPD and stable COPD. Main outcomes: Ratio of hs-cTnT in hospitalised AECOPD patients compared with stable COPD patients. Change in the ratio of hs-cTnT per unit increase of relevant covariables. Results: The geometric mean of hs-cTnT in the index group was 25.8 ng/l (95% CI 21.1 to 31.7) compared with 4.55 ng/l (95% CI 3.72 to 5.67) in the reference group. After inclusion of relevant covariables, multiple linear regression analyses showed that the ratio between hs-cTnT in AECOPD patients and the references was 4.26 (95% CI 3.02 to 6.00) and that hs-cTnT increased 1.41-fold (95% CI 1.20 to 1.68), for each quartile increase in leucocyte count in stable COPD but not in AECOPD. Higher hs-cTnT levels were also associated with the presence of pathological q-waves (p=0.012) and electrocardiographic left ventricular hypertrophy (p=0.039), long-term oxygen treatment (p=0.002) and decreasing forced expiratory volume in 1 s (p=0.014). A significant univariable association between cTnT and arterial hypoxaemia was also found but this association was attenuated almost to a zero effect after inclusion of relevant covariates. Conclusions: AECOPD is associated with higher hs-cTnT as compared with stable COPD. In stable COPD, hs-cTnT appears to be positively associated with indices of COPD severity, whereas we were unable to identify significant determinants of hs-cTnT in AECOPD.